The priority of management factors for reducing the yield gap of summer maize in the north of Huang-Huai-Hai region, China - Yue-e LIU; Yu-xin LI; Tian-fang LÜ; Jin-feng XING; Tian-jun XU; Wan-tao CAI; Yong ZHANG; Jiu-ran ZHAO; Rong-huan WANG (Journal of Integrative Agriculture, 2021)
Understanding yield potential, yield gap and the priority of management factors for reducing the yield gap in current intensive maize production is essential for meeting future food demand with the limited resources. In this study, we conducted field experiments using different planting modes, which were basic productivity (CK), farmer practice (FP), high yield and high efficiency (HH), and super high yield (SH), to estimate the yield gap. Different factorial experiments (fertilizer, planting density, hybrids, and irrigation) were also conducted to evaluate the priority of individual management factors for reducing the yield gap between the different planting modes. We found significant differences between the maize yields of different planting modes. The treatments of CK, FP, HH, and SH achieved 54.26, 58.76, 65.77, and 71.99% of the yield potential, respectively. The yield gaps between three pairs: CK and FP, FP and HH, and HH and SH, were 0.76, 1.23 and 0.85 t ha–1, respectively. By further analyzing the priority of management factors for reducing the yield gap between FP and HH, as well as HH and SH, we found that the priorities of the management factors (contribution rates) were plant density (13.29%)>fertilizer (11.95%)>hybrids (8.19%)>irrigation (4%) for FP to HH, and hybrids (8.94%)>plant density (4.84%)>fertilizer (1.91%) for HH to SH. Therefore, increasing the planting density of FP was the key factor for decreasing the yield gap between FP and HH, while choosing hybrids with density and lodging tolerance was the key factor for decreasing the yield gap between HH and SH.